Characterization of a novel EB1 acetylation site important for the regulation of microtubule dynamics and cargo recruitment. Issue 3 (25th September 2017) - Xie, Songbo; Yang, Yang; Lin, Xiaochen; Zhou, Jun; Li, Dengwen; Liu, Min
Abstract : Microtubule plus ends undergo highly dynamic modifications to regulate different aspects of cellular activities. Most microtubule plus‐end tracking proteins (+TIPs) are recruited to the microtubule ends by the master loading factor, end‐binding protein 1 (EB1). These proteins coordinately regulate microtubule dynamics and cellular plasticity. Acetylation is known to modulate EB1 function; however, the molecular details of EB1 acetylation remain largely unclear. We mapped the acetylation pattern of EB1 and identified several previously uncharacterized sites of EB1 acetylation. We examined the effects of lysine‐212 (K212) acetylation and found that acetylation of this site accelerates autophagy‐mediated EB1 degradation. By time‐lapse microscopy, we found that the acetylation‐deficient K212R mutant increased the percentage of fast‐growing and long‐lived microtubules. Although K212 acetylation did not affect microtubule stability in vitro and the association of EB1 with microtubules, the K212R mutant significantly promoted microtubule regrowth in cells. Coimmunoprecipitation assays further revealed that the K212 site was critical for the recruitment of different +TIP cargoes. These data thus uncover a critical role for a novel EB1 acetylation site in regulating the dynamic structure of microtubules. Abstract : In this study, the authors mapped the acetylation pattern of EB1 and identified several previously uncharacterized sites of EB1 acetylation. They found that acetylation of EB1 at K212 was important for the regulation of microtubule dynamics and cargo recruitment.